An interview study of consequences of early-career unemployment in Bulgaria - Krasteva, Veneta (Mednarodno inovativno poslovanje, 2018)
The article examines the consequences of prolonged unemployment experienced in the beginning of the career in Bulgaria from a subjective point of view. The analysis is based on information obtained from in-depth interviews with people from three age groups who have entered the labor market in periods with high levels of unemployment. The negative consequences pointed out by the interviewed people include material deprivation, limited access to health services, low self-esteem, interruption of social contacts, postponement of creating a family and living in a home of one's own, loss of hope for a better future. Along with the negative consequences, some positive ones were also identified, such as strengthening family ties, people's enhanced motivation to deal with the arising difficulties and their striving for personal development.
Keywords: Bolgarija; brezposelnost v zgodnji poklicni poti; Bulgaria; consequences; early-career unemployment; posledice; subjective assessment; subjektivna ocena